2017
DOI: 10.22452/jdbe.sp2017no1.5
|View full text |Cite
|
Sign up to set email alerts
|

Performance Comparison of Solar Assisted and Inverter Air-Conditioning Systems in Malaysia

Abstract: Heating, ventilation, and airconditioning (HVAC) systems account for approximately 55% of the total energy consumption in buildings. Different types of cooling technologies that integrate solar thermal energy have been explored because of increasing worldwide energy shortage. Latest airconditioning systems have achieved improved energy efficiency. The application of solar energy to various types of HVAC systems proved its huge potential for reducing energy usage. However, solar radiation is highly time depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Office building used solar-assisted AC [19], daylighting, and glazing [17], and for occupant behavior [24], [25] proved to use the same technique to reduce the energy consumption.…”
Section: Discussion On Saving Interest and Techniques Studies Accordi...mentioning
confidence: 99%
See 2 more Smart Citations
“…Office building used solar-assisted AC [19], daylighting, and glazing [17], and for occupant behavior [24], [25] proved to use the same technique to reduce the energy consumption.…”
Section: Discussion On Saving Interest and Techniques Studies Accordi...mentioning
confidence: 99%
“…The results indicated that the coefficient of performance (COP) for the solar-assisted AC ranged from 2.98 to 4.45 on the three days it was measured, proving to be energy efficient. When compared to an inverter AC unit, solar assisted AC proved to have considerably lower values of power usage on account of the PV panel [19].…”
Section: Active Strategiesmentioning
confidence: 92%
See 1 more Smart Citation
“…The results showed that the COP chiller ranged between 0.68 and 0.76 in 2018 and the electricity savings 41.1%. Munaaim M. et al [12] conducted a comparative study between solar assisted air conditioning and Inverter-type in the northern region of Malaysia, in Kedah where heating, ventilation, and air-conditioning (HVAC) systems consume approximately 55% in buildings. The results showed that the COP for solar air conditioning more than Inverter-type and the power consumption less than the Inverter-type.…”
Section: Introductionmentioning
confidence: 99%
“…From the latest product of portable air conditioning system design [16], [24]- [26], the heat waste is released to the surrounding in large amounts due to unorganized energy [27]- [32]. The thermal comfort zone standardized by The American Society of Heating, Refrigerating and Air-Conditioning Engineers (ASHRAE) is around 22 to 24 o C for most buildings in Malaysia [33]- [35]. Heat waste from the Peltier module spread to the air and cause uncomfortable to users.…”
Section: Introductionmentioning
confidence: 99%